ANALISIS IMPLEMENTASI METODE YANBU’A DALAM MEINGKATKAN PEMAHAMAN TAJWID SANTRI PONDOK PESANTREN DARUSY SYAFA’AH LAMPUNG TENGAH - Lia Gian Purwanto; Subandi Subandi; Ais Isti’ana (Jurnal Bilqolam Pendidikan Islam, 2026)
This study was motivated by the low ability of students in reading the Qur’an and understanding tajwid, particularly in the aspects of makharijul huruf, tajwid rules, shifatul huruf, bacaan gharib, and waqaf wa ibtida’. This study aimed to describe the implementation of the Yanbu’a method in improving students’ understanding of tajwid at Darusy Syafa’ah Islamic Boarding School and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative field research approach. Data were collected through observation, interviews, and documentation involving Yanbu’a halaqah teachers and students. Data analysis used the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The findings showed that the Yanbu’a method was implemented systematically through halaqah learning using talaqqi, musyafahah, sorogan, tashih, and muroja’ah methods. The method proved effective in improving students’ Qur’anic reading skills, especially in makharijul huruf, tajwid rules, shifatul huruf, bacaan gharib, and waqaf wa ibtida’. Supporting factors included teacher competence, direct practice-based learning, and a conducive Islamic boarding school environment, while inhibiting factors included differences in students’ basic abilities and limited learning time.